2021
DOI: 10.1021/acs.jproteome.1c00302
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals the Protein Regulatory Network of Anabaena sp. PCC 7120 under Nitrogen Deficiency

Abstract: Anabaena sp. PCC 7120 (Anabaena 7120) is a photoautotrophic filamentous cyanobacterium capable of fixing atmospheric nitrogen. It is a model organism used for studying cell differentiation and nitrogen fixation. Under nitrogen deficiency, Anabaena 7120 forms specialized heterocysts capable of nitrogen fixation. However, the molecular mechanisms involved in the cyanobacterial adaptation to nitrogen deficiency are not well understood. Here, we employed a label-free quantitative proteomic strategy to systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Here, we found that upstream of pecB , there are two putative RpaA binding sites ( P value = 1.5 × 10 −5 , Table S1). Since neither the abundance of RpaA nor its transcription decreases as a result of nitrogen deprivation ( 18 , 38 ), lower levels of pecBACEF transcription may be effected by a reduction in the levels of the active phosphorylated form (RpaA~P), which may be mediated by SasA and CikA in Anabaena as in S. elongatus ( 39 ). SasA is regulated in S. elongatus by the phycobilisome-associated B protein (RpaB), which is involved in the integration of temporal and environmental information and stress ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that upstream of pecB , there are two putative RpaA binding sites ( P value = 1.5 × 10 −5 , Table S1). Since neither the abundance of RpaA nor its transcription decreases as a result of nitrogen deprivation ( 18 , 38 ), lower levels of pecBACEF transcription may be effected by a reduction in the levels of the active phosphorylated form (RpaA~P), which may be mediated by SasA and CikA in Anabaena as in S. elongatus ( 39 ). SasA is regulated in S. elongatus by the phycobilisome-associated B protein (RpaB), which is involved in the integration of temporal and environmental information and stress ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here we found that upstream of pecB there are two putative RpaA binding sites (p value=1.5x10 -5 , Table S1). Since neither the abundance of RpaA nor its transcription decrease as a result of nitrogen deprivation (Camargo et al, 2021;Zhang et al, 2021), lower levels of pecBACEF transcription may be effected by a reduction in the levels of the active phosphorylated form (RpaA~P), which may be mediated by SasA and CikA in Anabaena as in S.…”
Section: Discussionmentioning
confidence: 99%
“…Here we found that upstream of pecB there are two putative RpaA binding sites (p value=1.5×10 -5 , Table S1). Since neither the abundance of RpaA nor its transcription decrease as a result of nitrogen deprivation (Camargo et al, 2021; Zhang et al, 2021), lower levels of pecBACEF transcription may be effected by a reduction in the levels of the active phosphorylated form (RpaA~P), which may be mediated by SasA and CikA in Anabaena as in S. elongatus (Gutu and O’Shea, 2013). SasA is regulated in S. elongatus by the phycobilisome-associated B protein (RpaB), which is involved in the integration of temporal and environmental information and stress (Espinosa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As cyanobacteria are exposed to dynamic environmental conditions, they have developed sophisticated defense and detoxification systems to ameliorate the consequences of stress-induced reactive oxygen species (ROS). While the dynamics of cyanobacterial intracellular processes related to stress responses has been studied intensively ( 1 12 ), there are significant gaps in our understanding of the stresses managed in the extracellular space. In addition to a variety of exometabolites, cyanobacterial extracellular milieu is rich in proteins, whether they are actively secreted or not ( 13 18 ).…”
Section: Introductionmentioning
confidence: 99%